MENGGABUNGKAN MANAJEMEN PEMASARAN DAN E-BISNIS UNTUK MEMAHAMI PERMINTAAN PASAR - Patricia Channelia Wea; Hendra Dwi Prasetyo; Ari Susanto; Burhan Safrezar (PUTRA JAWA PUBLISHER, 2024)
In the ever-evolving digital age, the integration between marketing and e-business management is becoming increasingly important for companies to understand and respond effectively to market demands. The combination of these two fields allows companies to optimize their marketing strategies and gain a competitive advantage. The following are some of the ways in which marketing and e-business management can work together to understand market demand. By combining marketing and e-business management, companies can gain a deeper understanding of market demand and design more effective strategies to meet customer needs. This enables companies to remain competitive in an ever-changing business environment and improve overall customer satisfaction. The use of information technology, particularly in the form of e-business, has significantly changed the business landscape, including in the context of marketing management. This study aims to investigate how the integration between marketing management and e-business can be used to understand market demand more effectively. Through a literature review approach, this article reviews relevant concepts and strategies in combining marketing management and e-business, and highlights their practical implications in analyzing and responding to changes in market demand. The results show that this integration enables companies to be more responsive to customer needs and preferences, improve the accuracy of demand predictions, and strengthen their competitive position in an increasingly digitalized market. In conclusion, the merging of marketing and e-business management is an important approach in optimizing business strategies and meeting the challenges of understanding and keeping up with dynamic market demand changes.